A Model Development And Comparison Study On The Microwave Remote Sensing Of Snow Medium Using A Coupled Finite Element Method And Method Of Moment, And The Relaxed Hierarchical Equivalent Source Algorithm - Hamsalekha, Kumaresan (2022)
Active microwave remote sensing is essential to analyze the condition of the earth’s terrain by investigating the return of microwaves from the mentioned environment. The forward model is crucial to compute the backscattering return of the earth terrain under inv estigation, allowing comparison with the satellite data as it can be utilized in the inverse model to retrieve other earth terrain parameters. Radiative transfer equation is applied in the active remote sensing to calculate the backscattering coefficient f or the theoretical model of the earth topographies such as vegetation, soil, snow medium and other earth terrains. Computational Electromagnetics Method (CEM) is vital to construct a more detailed shape of the scatterers and offer a better knowledge of the interaction between microwave radiation and the medium by considering the coherent effect of the dense snow medium. In this study, the secondorder radiative transfer equation is incorporated with the theoretical model of the snow medium. The investigatio n is done by integrating two computational techniques, which are the coupled Finite Element Method (FEM) and Method of Moment (MoM) and the Relaxed Hierarchical Equivalent Source Algorithm (RHESA). These CEM generated electric and magnetic fields will be ncorporated with the Dense Medium Phase Amplitude Correction Theory (DMPACT). These theoretical models consist of six shapes of scatterers which characterize the ice particles in the snow medium. These mentioned shapes are sphere, cylinder, peanut, hexago nal column, droxtal and ellipsoid. These techniques are used to study the effect of the various incident angles, layer thickness and frequencies of the backscattering mechanism. In previous investigations, little work has been carried out on the secondord er radiative transfer equation on various shapes of ice scatterers by incorporating DMPACT and Integral Equation Method (IEM) in snow medium. In this research, two different CEM techniques are incorporated into six different shapes of ice scatterers by in corporating DMPACT and IEM, and the accuracy of the CEM techniques is studied. Through analysis, it is found that the discrepancy of the backscattering coefficient generated by coupled FEM/MoM with Mie theoretical result is higher than the discrepancy bet ween RHESA and Mie theoretical result, especially at higher frequency and layer thickness of snow medium. The number of unknowns and the order of basis functions vary between these two CEM techniques, and these factors affect the accuracy of the results. T he accuracy of the backscattering coefficient results generated by CEM techniques will be further justified by comparing them with the ground truth measurements. Through this research, a suitable CEM technique can be chosen for future investigation for oth and different terrains.